Revisiting Jacques Gréber's L’Architecture aux États-Unis : From City Beautiful to Cité-Jardin - Gournay, Isabelle (Urban History Review / Revue d'histoire urbaine, 2001)
In 1920, Jacques Gréber published what was and still is the largest book on U.S. architecture and urban design ever issued in France. His dual agenda was to stress the impact of Beaux-Arts design methods (presenting his gardens and Philadelphia parkway as highlights of this trend), and to advocate the practical accomplishments of a pragmatic and affluent civilization.Showcasing an "edited" North American city, devoid of commercialism and filled with civic structures of great dignity and comfort, L'Architecture aux États-Unis looked back to ideals and accomplishments of the American Renaissance and ahead to the metropolitan culture of the 1920s. For the first time in France, ventures by U.S. architects in the field of civic art were acknowledged as major achievements. Gréber formulated ideas about modern North American civic centres, business districts, parks, and model suburbs that would affect his proposals for Ottawa and on his French career. His book triggered the evolution of French views of the U.S.-built environment toward greater interest and generally more positive views.